Baat se baat - Syed, Shamoon; Beenish, Qureshi (book group Karachi, 2003)
"Baat Se Baat" by Syed Shamoon is a children's book designed to enhance reading and writing skills in young learners. It features illustrated stories that are engaging and easy to understand. The book aims to spark children's imagination and encourage a love for reading.